2010
DOI: 10.1103/physrevb.81.224107
|View full text |Cite
|
Sign up to set email alerts
|

Langevin model for real-time Brownian dynamics of interacting nanodefects in irradiated metals

Abstract: In situ real-time electron microscope observations of metals irradiated with ultrahigh-energy electrons or energetic ions show that the dynamics of microstructural evolution in these materials is strongly influenced by long-range elastic interactions between mobile nanoscale radiation defects. Treating long-range interactions is also necessary for modeling microstructures formed in ex situ high-dose-rate ion-beam irradiation experiments, and for interpolating the ion-beam irradiation data to the low-dose-rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 62 publications
6
46
0
Order By: Relevance
“…Any correlation arising from their interaction may be eliminated by analyzing the center of massx, defined here to be the mean of the two kink positions,x = (x (1) + x (2) )/2. It may be shown 24,25 that such a quantity is independent of any interaction, and it yields a diffusion constant one half that of a free kink, D kink /2. Thus we construct from the two kink positions a single time series {x n∆t }, n = 0, 1, ...N for the center of mass to ensure such correlation effects do not affect our results.…”
Section: Molecular Dynamics Simulation Of Thermally Fluctuating DImentioning
confidence: 99%
“…Any correlation arising from their interaction may be eliminated by analyzing the center of massx, defined here to be the mean of the two kink positions,x = (x (1) + x (2) )/2. It may be shown 24,25 that such a quantity is independent of any interaction, and it yields a diffusion constant one half that of a free kink, D kink /2. Thus we construct from the two kink positions a single time series {x n∆t }, n = 0, 1, ...N for the center of mass to ensure such correlation effects do not affect our results.…”
Section: Molecular Dynamics Simulation Of Thermally Fluctuating DImentioning
confidence: 99%
“…These energies vary from a fraction of an eV to several eV [1,2]. The energy scales of elastic interactions between defects are similar, depending on the size of defects and the distance between them [3,4]. Whereas the spectrum of activation energies for 15 reactions between defects is discrete, the energies of elastic interactions are distributed continuously.…”
mentioning
confidence: 99%
“…Langevin dynamics simulations of mobile elastically interacting nano-defects [3,4] show that these interactions strongly influence the evolution of microstruc-40 ture, leading to trapping of defects, and giving rise to defect clustering and the formation of rafts of defects. Rafts of defects are routinely observed experimentally in materials exposed to irradiation [20,21,22,23,24,25,26].…”
mentioning
confidence: 99%
“…The resulting data can be deployed as an input for the theoretical models of long time evolution of damaged material. 3,14,33,34 It was shown that both the SIAs and the vacancy loops have high one-dimensional (1D) mobility along close-packed crystal directions in bcc crystals. 10,31,32 The small clusters can switch their propagation direction between equivalent directions, which result in the three-dimensional (3D) diffusion at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%